2020
DOI: 10.1155/2020/7815214
|View full text |Cite|
|
Sign up to set email alerts
|

Alterations of Several Serum Parameters Are Associated with Preeclampsia and May Be Potential Markers for the Assessment of PE Severity

Abstract: The precise pathophysiological mechanisms of preeclampsia (PE) and preventative strategies remain unknown. Laboratory markers which can help in identifying PE patients from pregnant women and assessing the severity of PE during pregnancy are worthy to be explored. In this study, a retrospective case-control study was designed to assess whether the serum levels of albumin (ALB), total protein (TP), prealbumin (PA), alkaline phosphatase (ALP), lactic dehydrogenase (LDH), D-dimer, fibrinogen (Fbg), platelet (PLT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 39 publications
3
21
1
Order By: Relevance
“…reported no significant difference in PCs and MPV with the presence of preeclampsia or with the severity of preeclampsia. [ 23 ] In our study, in preeclampsia patients, RDW had a significant difference from controls, and our findings matched with one meta-analysis which concluded that the RDW level is higher in SPE as compared to NSPE. [ 24 ] In our study, RDW predicts NSPE and SPE with 85.3% and 93.8% sensitivity, specificity 49%, and 44.1%, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…reported no significant difference in PCs and MPV with the presence of preeclampsia or with the severity of preeclampsia. [ 23 ] In our study, in preeclampsia patients, RDW had a significant difference from controls, and our findings matched with one meta-analysis which concluded that the RDW level is higher in SPE as compared to NSPE. [ 24 ] In our study, RDW predicts NSPE and SPE with 85.3% and 93.8% sensitivity, specificity 49%, and 44.1%, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…The sensitivity of LDH in predicting preeclampsia was reported in four articles that were particularly heterogeneous due to the quite heterogeneous optimal cut-off values that were evaluated; thus, precluding analysis of results. Specifically, Duan et al reported an area under the curve (AUC) that reached 0.899 and a sensitivity of 92.5% using a cut-off value of 183.5 U/L [20]. Similarly, Khalil observed that LDH could help differentiate severe preeclampsia from healthy controls as well as patients with proteinuria, gestational hypertension and mild preeclampsia using a cut-off value of 208 U/L (sensitivity 100%, AUC 71.2%) [21].…”
Section: Qualitative Analysismentioning
confidence: 99%
“…PE progresses rapidly. There are currently no specific laboratory indicators to diagnose and grade the severity of PE patients, which may have an impact on the subsequent treatment of patients (8,9). The anti-angiogenic factor sFlt-1 is secreted by the placenta and is involved in vascular regulation.…”
Section: Discussionmentioning
confidence: 99%